Mesh construction and computational analysis of the biomechanics of an endovascular intervention in cerebral aneurysms using Kirchhoff–Love shells - Muzi, Nicolás (2021)
The mechanism of aneurysm rupture is still not fully understood. The rupture risk of the intervention may increase during endovascular occlusions of cerebral aneurysms due to a localized load in the parent vessel close to the neck, a common day-to-day situation. As a first attempt on the road towards developing a plausible analysis capable of dealing with many cases in a statistical sense, we describe the deformation kinematics using a geometrically nonlinear thin shell model under Kirchhoff-Love’s assumptions in conjunction with a simplistic Kirchhoff-St. Venant’s hyperelastic material model. Though it cannot assess the artery’s complexity, this more straightforward yet not trivial approach enable us to statistically study the application of a concentrated load in many locations, which mimics the action of an instrument during the endovascular treatment. We performed numerical simulations on 34 cases from the AneuriskWeb Database. We present preliminary results considering a smoothly varying thickness between the parent vessel and the aneurysm dome, focusing in the mesh construction process and loading.